2019
DOI: 10.1021/acs.jnatprod.9b00693
|View full text |Cite
|
Sign up to set email alerts
|

Kalshinoids A–F, Anti-inflammatory Sesquiterpenes from Kalimeris shimadae

Abstract: In a study of the potential anti-inflammatory constituents from Kalimeris shimadae, six new sesquiterpenes, kalshinoids A–F (1–6), together with 21 known compounds (7–27), were isolated. The structures and absolute configurations of the new compounds were discerned from extensive spectroscopic analysis, and the absolute configurations of kalshinoids A, B, E, and F were established by ECD calculations. Furthermore, the identified compounds were tested for anti-inflammatory activity as assessed by inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The 13 C‐NMR ( Table 1) and HSQC spectroscopic information of 3 could be assigned for 15 carbon signals, including two olefinic carbons ( δ C 139.6 and 124.3), five methylene groups ( δ C 67.4, 42.9, 27.6, 23.5 and 23.0), four methine groups ( δ C 51.2, 48.1, 40.9, and 27.2), a quaternary carbon ( δ C 72.9), and three methyl groups ( δ C 21.9, 20.5 and 15.5). Comprehensive analysis of NMR data demonstrated that 3 had a same planar structure as 10β,15‐hydroxy‐α‐cadinol, [13] and then this conclusion was verified via the detailed 2D NMR correlation ( Figure 2). The difference being the presence of the NOE correlation between H‐1 and H‐14, and the difference of spatial configuration of 3 was demonstrated based on a NOESY test.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The 13 C‐NMR ( Table 1) and HSQC spectroscopic information of 3 could be assigned for 15 carbon signals, including two olefinic carbons ( δ C 139.6 and 124.3), five methylene groups ( δ C 67.4, 42.9, 27.6, 23.5 and 23.0), four methine groups ( δ C 51.2, 48.1, 40.9, and 27.2), a quaternary carbon ( δ C 72.9), and three methyl groups ( δ C 21.9, 20.5 and 15.5). Comprehensive analysis of NMR data demonstrated that 3 had a same planar structure as 10β,15‐hydroxy‐α‐cadinol, [13] and then this conclusion was verified via the detailed 2D NMR correlation ( Figure 2). The difference being the presence of the NOE correlation between H‐1 and H‐14, and the difference of spatial configuration of 3 was demonstrated based on a NOESY test.…”
Section: Resultsmentioning
confidence: 74%
“…The presence of NOE correlations between H-1/H-6, H-1/H-10/H-13, and H-12/H-14 (Figure 3 quaternary carbon (δ C 72.9), and three methyl groups (δ C 21.9, 20.5 and 15.5). Comprehensive analysis of NMR data demonstrated that 3 had a same planar structure as 10β,15-hydroxy-α-cadinol, [13] and then this conclusion was verified via the detailed 2D NMR correlation (Figure 2). The difference being the presence of the NOE correlation between H-1 and H-14, and the difference of spatial configuration of 3 was demonstrated based on a NOESY test.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The NOESY correlations ( Figure 3) of H‐1 β/ Me‐14 and H‐1 α /H‐5 indicated Me‐14 and H‐5 to be β ‐ and α ‐oriented, respectively. Comparing CD data with known compound, it was verified that the absolute configuration of 2 was 5 S ,10 S [11] …”
Section: Resultsmentioning
confidence: 88%